Deciphering the population dynamics and drug-resistance characteristics of extrapulmonary tuberculosis: genomic and clinical insights from a Chinese hospital - Gong, Shiwei; Li, Xinyue; Rao, Youyi; Chen, Jun; Hu, Yanjie; Guo, Jianjian; Wang, Kai; Liu, Chang; He, Qian; Zhao, Yanlin; Ren, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionExtrapulmonary tuberculosis (EPTB) is characterized by atypical clinical symptoms, difficult diagnosis, and high mortality, so it is very important to know the prevalence and drug resistance (DR) status. MethodsThis study analyzed 427 isolates of EPTB from a Chinese hospital. Drug susceptibility testing for widely used anti-TB drugs was performed. All isolates were subjected to whole-genome sequencing (WGS) to explore the molecular characteristics of resistance and to perform phylogenetic analysis. Clinical characteristics and DR patterns associated with Mycobacterium tuberculosis (MTB) lineages were evaluated using chi-square analysis, and associations with DR-EPTB were assessed using multinomial logistic regression.ResultsThe number of EPTB strains exhibited a general upward trend, and most EPTB cases in this study were accompanied by PTB. The predominant types were tuberculosis of urinary system (29.98%), tuberculous meningitis (23.65%), and lymph node tuberculosis (22.72%). Quadratic regression revealed a decline in urinary system cases and an increase in lymph node cases. Lineage 2 accounted for 83.60% of isolates and was significantly associated with isoniazid (INH) and streptomycin (STR) resistance. Overall resistance rates were 13.58% for INH and 7.73% for rifampicin (RIF). Male sex was associated with higher DR risk (aOR = 1.63, p = 0.046). Common resistance mutations included katG Ser315Thr, rpoB Ser450Leu, and gyrA mutations. The clustering rate was 19.67%, indicating limited recent transmission.DiscussionThe predominance of lineage 2 and high rates of anti-tuberculosis drug resistance indicate that EPTB remains a clinically and epidemiologically significant problem.